TINJAUAN PELAKSANAAN PEMELIHARAAN DOKUMEN REKAM MEDIS DI RUANGAN FILLING RUMAH SAKIT DR.PIRNGADI MEDAN TAHUN 2019 - Esraida Simanjuntak; Rizka Mei Shella (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
Maintenance of medical record documents is a combination of various activities undertaken to maintain documents and production facilities including other production equipment or to repair them to a condition that is well accepted. Physical danger is damage to documents caused by sunlight, rain, flood, heat and humidity. Chemical hazard is document damage caused by food, beverages, and chemicals. Biological hazard is document damage caused by rats, cockroaches, and termites. The purpose of this study is to describe the implementation of maintenance of medical record documents in the room Dr. hospital filling Pirngadi Medan in 2019. This type of research is a description of the interview and observation methods. The place of research was conducted at Dr. Pirngadi Medan due to the inability of maintaining medical record documents. When the study was conducted in March-April 2019. Population and samples used were all medical record storage officers, amounting to 3 people. Based on the results of the study, there were still racks that used wood and did not use rool o'pack cabinets, there are damaged medical record documents that have not been replaced with new ones due to lack of cover inventory. The temperature and humidity of the room in the storage room are less controlled. The conclusion of this study is that the maintenance of medical record documents has not been carried out because the shelves are still made from wood and the lack of storage rack facilities make medical records documents partially placed under the floor. The suggestion from this research is that it is better to use a rool o'pack cupboard and keep the air conditioner on for 24 hours according to the theory.